Human T-Cell Lymphotropic Virus Types 1 and 2 Seropositivity among Blood Donors at Mbarara Regional Blood Bank, South Western Uganda - Tweteise, Patience Uchenna; Natukunda, Bernard; Bazira, Joel (Leukemia research and treatment, 2016)
Background. The human T-cell lymphotropic virus types 1 and 2 (HTLV 1/2) are retroviruses associated with different pathologies.HTLV-1 causes adultT-cell leukemia/lymphoma(ATL) andHTLV-1-associatedmyelopathy/tropical spastic paraparesis (HAM/TSP); HTLV-2 is not clearly associated with a known clinical disease. Both viruses may be transmitted by whole blood transfusion, from mother to child predominantly through breastfeeding, and by sexual contact. Presently, none of the regional blood banks in Uganda perform routine pre-transfusion screening for HTLV. The aim of this study was to determine the prevalence of antihuman T-cell lymphotropic virus types 1/2 (HTLV-1/2) antibodies among blood donors at Mbarara Regional Blood Bank in South Western Uganda. A cross-sectional study was conducted between June 2014 and September 2014. Methodology. Consecutive blood samples of 368 blood donors were screened for anti-HTLV-1/2 antibodies using an enzyme linked immunosorbent assay (ELISA). Samples reactive on a first HTLV-1/2 ELISA were further retested in duplicate using the same ELISA. Of the three hundred and sixty-eight blood donors (229 (62.2%) males and 139 (37.8%) females), only two male donors aged 20 and 21 years were HTLV-1/2 seropositive, representing a prevalence of 0.54%. Conclusion.HTLV-1/2 prevalence is low among blood donors at Mbarara Regional Blood Bank. Studies among other categories of people at risk for HTLV 1/2 infection should be carried out.
Keywords: Human T-Cell; Lymphotropic Virus; Blood Bank